The Churching of Colonial Connecticut: A Case Study - Hull, Brooks Brittenham (Review of religious research, 1999)
The market model of religion asserts in part that clergy respond to incentives. For eighteenth-century European established churches, clergy income was independent of church membership and so clergy tended not to behave in a manner attractive to potential members. By contrast, the established Congregational (Puritan) church of colonial Connecticut featured a structure that rewarded to a significant degree zealous clergy. Clergy were hired and fired at the local level by community members who also voted on local clerical taxes. The market model thus predicts relatively strong church membership. Archival data show that the number of new Puritan congregation members as a share of population remained relatively constant over time. The number of new members of individual established congregations remained constant. Church membership was often high in colonial Connecticut towns. Entry by nonestablished congregations had only a modest negative effect on Puritan membership.